Cover Image. (3rd April 2023) - Hu, Yiting; Dong, Fang; Xue, Ting; Zhou, Mi; Huang, Ruoyan; Sui, Feng; Guo, Qiang; Hou, Wenbao; Cai, Wenlong; Yuan, Kai; Wang, Hongde; Yu, Dahua
Abstract : The cover image is based on the Original Article Glutamate levels in the ventromedial prefrontal cortex and resting‐state functional connectivity within reward circuits in alcohol‐dependent patients by Yiting Hu et al., https://doi.org/10.1111/adb.13272 .